PENGARUH UKURAN PERUSAHAAN, PERTUMBUHAN PERUSAHAAN DAN UKURAN KAP TERHADAP AUDITOR SWITCHING - Rezy Reno Bulan Mulyadi; Suyanto Walidi (Jurnal Akrab Juara, 2019)
This study aims to investigate the influence of net Income, comprehensive income, other comperhensive Income, SEC (Components from other comprehensive Income with low subjectivity) and N_SEC (Components from other comprehensive Income with high subjectivity) to stock return in mining companies listed on the Indonesia Stock Exchange in 2011 – 2015.This study uses quantitative data that have been published in the Indonesia Stock Exchange ( BEI ) . The samples used in this study were 164 , including 41 companies that met the study criteria , as this study using purposive sampling method in sample selection . While the method of data analysis using panel data regression techniques with Eviews 9.0 application.The result of tests performed by using chow test and Hausman test choose better random effect model. Results in partial test (t test) obtained that net Income, comprehensive income, and N_SEC (Components from other comprehensive Income with high subjectivity) to stock return, while the other comperhensive Income, and SEC (Components from other comprehensive Income with low subjectivity) has no effect on stock return . While the results of simultaneous ( F test ) obtained net Income, comprehensive income, other comperhensive Income, SEC (Components from other comprehensive Income with low subjectivity) dan N_SEC (Components from other comprehensive Income with high subjectivity) has no simultan effect to stock return . Where the error rate used is 5 % or 0.05 at significant level of 95%